Comparing Treatment with Nebulized 3% Hypertonic Saline Versus Nebulized 0.9% Saline In Patients With Acute Bronchiolitis: A Double-Blind Randomized Controlled Trial - Abid, Uzma; Afzal, Ayesha; Zaman, Nahdia; Farooq, Ammara; Yousaf, Sidrah; Fazal, Sonia (Journal of Rawalpindi Medical College, 2024)
Objective: To establish the therapeutic role of nebulized hypertonic saline solution in the management of acute bronchiolitis in terms of primary and secondary outcomes. Methods: This randomized control trial was conducted in the Pediatric department of Holy Family Hospital, Rawalpindi for 8 months from September 2021 to April 2022 after ethical approval. A total of 65 cases of acute bronchiolitis were enrolled who were divided into two groups. The intervention group was nebulized with 3 ml of 3% hypertonic saline 6 hourly while the control group was nebulized with 0.9% saline 6 hourly during hospital stay in addition to the standard treatment. Children in both groups were monitored in terms of clinical severity score, feeding, hydration status, length of hospital stay, duration of oxygen supplementation, development of any adverse effect, and outcome (length of hospital stay and clinical severity score) was observed. Data was collected on a predesigned proforma, and SPSS version 21 was used to analyze the data. Results: Two groups were comparable for age, gender, and baseline characteristics including clinical severity score. Length of hospital stay was significantly less in the hypertonic saline group 75.53 ±43 .87 versus 45.92 ± 12.19 (p-value 0.000). Similarly, in patients requiring oxygen, treatment with hypertonic saline significantly reduced the duration of nebulization, 27.21 ±26.20 versus 10.67± 7.91 (p-value 0.03). However clinical severity score between the two groups was not different, 5.42 ± 2.88 in the saline group and 4.50 ± 2.88 p value 0.921. Conclusion: Nebulization with hypertonic saline reduces oxygen requirement and benefits in reducing the length of hospital stay. Keywords: Bronchiolitis, Hypertonic saline (HS), Normal saline (NS)